(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2018)
The study addressed refers to the analysis of the application of the new consumption tax approved in the modification of the Tax Statute established in Law 1607 of 2012, the analysis covers the owners of 104 restaurant service companies in the Municipality of Florencia Caquetá, period 2013-2014. A survey was applied whose statistical analysis was done through the SPSS package, which covers all the elementary aspects for the preparation of graphs and descriptive statistics. The results show that of the companies surveyed and belonging to the Common Regime, 78% of the establishments are up to date with the submission of bimonthly excise tax returns and the remaining 22% did not answer, which allows us to establish that there is still ignorance of the rule and have had difficulty in knowing the rule to give applicability with this new tax obligation.